Volyn within the Russian Empire: Migratory Processes and Cultural Interaction - Nadolska, Valentyna V.; Надольська, Валентина Василівна (Slavic Research Center, 2007)
Ethnic-cultural mutual influences of native Ukrainians, Poles, Jews, Czechs and Germans, who put their mark over the language, economy, material and spiritual culture of contacting ethnic groups, which are typical for long-term historical development are analysed in the article.
Keywords: Germans; Cheches; Poles; Jewes; cultural interaction; Volyn